The efficacy of Isotretinoin-loaded solid lipid nanoparticles in comparison to Isotrex® on acne treatment - Pouran Layegh; Navid Mosallaei; Danial Bagheri; Mahmoud Reza Jaafari; Shiva Golmohammadzadeh (Nanomedicine Journal, 2013)
Abstract: Topical retinoids are considered as the first line therapy in the treatment of acne vulgaris, but they are associated with cutaneous irritation. In this study, isotretinoin-loaded solid lipid nanoparticles(IT-SLN) were prepared to treat the mild to moderate acne. Also using IT-SLN would minimize IT adverse effects in comparison to commercial product, Isotrex®. This study was conducted to prepare and characterize IT-SLN and assessing the efficiency of IT-SLN comparing to Isotrex® acne. IT-SLN was prepared using hot high pressure homogenization method.  IT-SLN contained 0.05% IT in 5% of lipid phase (Glyceryl monostearate- GMS) and tween 80 (2.5 % w/v) was used as surfactant in the aqueous phase. IT-SLN was characterized by particle size analyzing, differential scanning calorimetry and transmission electron microscopy. Encapsulation efficacy was also obtained using spectrophotometry. The efficacy of IT-SLN was evaluated in a randomized, single-blind, parallel-group study and compared with Isotrex®. Forty patients encountered in the study and divided in two groups. Treatment regimen was once-nightly topical administration accompanied with topical administration of clindamycin 2% solution twice a day for 8 weeks. The particle size of IT-SLN was around 60 nm with PDI of 0.4 and zeta potential was about -40 mV. Encapsulation efficacy of IT in SLN in crystalline form was 84±0.21%. IT-SLN produced significantly better treatment than Isotrex® in both non-inflammatory and inflammatory lesions according to its recovery percent after 8 weeks. Also IT-SLN gained better global assessment scores. Our results showed that IT-SLN had higher efficacy than Isotrex® to clear non-inflammatory and inflammatory lesions.